Beyond Expectation : Assisted Conception and the Politics of Recognition - Luce, Jacquelyne Marie, 1971- (Book collections on Project MUSE., 2010)
An in-depth study of lesbian, bi, and queer women's experiences of thinking about and trying to become a parent, Beyond Expectation draws on eighty-two narrative interviews conducted during the late 1990s in British Columbia.